2020
DOI: 10.3389/fvets.2020.00060
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Attitudes of Communities to the Social, Economic, and Cultural Importance of Working Donkeys in Rural, Peri-urban, and Urban Areas of Ethiopia

Abstract: Working donkeys (Equus africanus asinus) are vital to the development and support of people's livelihoods in rural, peri-urban, and urban areas of Ethiopia. However, despite their critical role in providing transport, food security, and income generation to some of the poorest and most marginalized households, donkey contributions to human livelihoods have been largely unexplored. Donkey users, veterinary surgeons, business owners, and civil servants were interviewed to investigate the role humans play in shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 12 publications
(15 reference statements)
1
37
0
Order By: Relevance
“…The qualitative data further demonstrate how rural people value the donkey as an indicator of social status, means of transportation and an economic asset. This correlates with the findings of Geiger et al (2020) in a study conducted on the importance of working donkeys in rural areas of Ethiopia. The study found that donkeys are an important support in rural, peri-urban and urban settings through the creation of economic security, independence and participation in local saving schemes.…”
Section: The Importance Of Donkeys In the Areasupporting
confidence: 90%
“…The qualitative data further demonstrate how rural people value the donkey as an indicator of social status, means of transportation and an economic asset. This correlates with the findings of Geiger et al (2020) in a study conducted on the importance of working donkeys in rural areas of Ethiopia. The study found that donkeys are an important support in rural, peri-urban and urban settings through the creation of economic security, independence and participation in local saving schemes.…”
Section: The Importance Of Donkeys In the Areasupporting
confidence: 90%
“…Households with donkeys were more likely to consume poultry, meat and eggs than households without donkeys. Studies (58–61) from Ethiopia have identified that donkeys contribute to human livelihood and household food security through their role in income generation and gender empowerment. This might have contributed to the observed positive association between donkey ownership and ASF consumption frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…The words used by the soldiers to describe the mules they work with differ from those used by urban working horses asked the same question, where horses are viewed as a friend, family member and important income generation tool [ 26 ]. One important difference between the present study and previous ones studying perceptions towards working or pleasure/sport equids [ 21 , 56 ] is that, in the case of the army mules, the caretakers are not the owners and do not receive direct income from the mules. Such fact could be the main difference in the perception and attitudes towards them, resulting in a more instrumental and utilitarian view.…”
Section: Discussionmentioning
confidence: 70%